Analysis of Unused Organ Donors in the Netherlands: Older Donor Age Associated With Higher Risk of Non-Utilization - K. A. Chotkan; K. A. Chotkan; M. A. Kuiper; M. A. Kuiper; I. P. J. Alwayn; I. P. J. Alwayn; M. B. A. Heemskerk; A. E. Braat; A. E. Braat; N. E. Jansen (Transplant International)
This study aims to provide objective evidence for the subjectively observed increase in non-utilized donors and to investigate whether they share common risk factors, hypothesizing that the aging of the donor population may be a possible explanation. All referred deceased donors in the Netherlands between 2018 and 2023 were analyzed. A utilized donor was defined as a referred donor that resulted in at least one transplanted organ. A non-utilized donor was defined as a donor from whom no organ was transplanted as a result of the cessation. In total, 2,235 donors were defined as referred; 1,618 donors were utilized and 617 were non-utilized. A significant increase in referred donors aged >66 years was observed, together with an increase of 51% in non-utilized donors. The most frequent reasons for not utilizing a donor were found to be an agonal phase > 2 hours in DCD donors (45%) and an unacceptable medical history at screening (22%). Multivariable logistic regression analysis showed that increasing donor age (age 66–75 years OR 1.81, 95% CI 1.09–3.00), DCD donors (OR 4.37 95% CI 3.24–5.89, p < 0.01), history of hypertension (OR 1.29 95% CI 1.01–1.66, p = 0.04) and/or diabetes (OR 2.48 95% CI 1.75–3.51, p < 0.01) were associated with non-utilization. Non-utilized donors are significantly older, are more often DCD donors and have more co-morbidities, confirming the hypothesis that these donors are the more marginal donors.